2013
DOI: 10.1039/c3ra43830a
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic self-cleaning antireflective coatings on Fresnel lenses by integrating hydrophilic solid and hydrophobic hollow silica nanoparticles

Abstract: Superhydrophobic self-cleaning antireflective coatings were fabricated on Fresnel lenses by integrating solid silica nanoparticles (SSNs) and stearic acid (STA) and 1H,1H,2H,2H-perflurooctyltriethoxysilane (POTS) co-modified hollow silica nanoparticles (SPHSNs) via spin-and spray-assembly without any high temperature pre-or post-treatment. Transmission electron microscopy (TEM) was used to observe the morphology and structure of nanoparticles. Transmission spectra were recorded using a UV-Vis-NIR spectrophotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Inspired by nature, many efforts have been made in the last two decades to develop artificial superhydrophobic surfaces on engineering materials for various practical applications, such as self‐cleaning, anti‐icing, anticorrosion, and fluid drag reduction . The first artificial superhydrophobic surface was reported in 1996 by Onda et al, who demonstrated a superhydrophobic surface of alkylketendimer with fractal surface morphology exhibiting a water contact angle as high as 174°.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by nature, many efforts have been made in the last two decades to develop artificial superhydrophobic surfaces on engineering materials for various practical applications, such as self‐cleaning, anti‐icing, anticorrosion, and fluid drag reduction . The first artificial superhydrophobic surface was reported in 1996 by Onda et al, who demonstrated a superhydrophobic surface of alkylketendimer with fractal surface morphology exhibiting a water contact angle as high as 174°.…”
Section: Introductionmentioning
confidence: 99%
“…(e, h) 2D views of grating diffraction in a semi-transparent globe using 533 and 450 nm beams at normal incidence illumination (scale bar= 2 cm). (f, i) The angle of diffraction pattern from the grating illuminated normally at λ=450 and 533 nm.To simulate the diffraction effect, the Geometrical Theory of Diffraction GTD was used[53]. The effect of the two-dimensional groove was modeled with a two-dimensional phase modulation in a plane.…”
mentioning
confidence: 99%
“…However, the additional removal step of sacrificial templates usually requires high temperature, which is undesirable for certain polymer substrates, and raises environmental and energy issues. The third one is to combine improved hydrophobicity with closed pore structure [25][26][27]. Unfortunately, the above organic-modified surfaces required extra-organic reaction using fluoro-materials on nanoparticles and could be difficult to control the surface characteristics.…”
Section: Introductionmentioning
confidence: 98%